EFFECTIVITY REGULATION OF THE MINISTER OF HOME AFFAIRS IN THE MANAGEMENT OF REGIONAL ASSETS IN BATU CITY - Hendra Saputra Jaya; Catur Wido Haruni; Sholahuddin Al-Fatih (Indonesia Law Reform Journal, 2021)
Regional assets are regional wealth earned from spending using APBD and grants. Therefore, regional asset management must be professional and modern oriented towards good government. Technically asset management in each region refers to Regulation of The Minister of Home Affairs No. 16 Year 2019 On the Management of Regional Assets. This research discusses the asset management of Batu City area using sociological juridical research methods that raise the issue of asset management barriers and the effect of asset management in Batu City. This research shows that; First, there are barriers in terms of human resources, both in understanding the rules as well as on the understanding related to administration that impacts on the disorder of the administration until now. Second, asset management in Batu City has not been effective because there has not been a clear measure that is used as a guideline for the assessment of effectiveness but only based on compliance with the rules.